Induction Spot Welding of Metal/CFRPC Hybrid Joints1. Issue 9 (29th January 2013) - Mitschang, Peter; Velthuis, Rudi; Didi, Mirja
<x xml:space="preserve">Abstract</x> Today's areas of application for lightweight materials range from consumer goods and sports to high technology applications in transportation like aerospace or automotive. Thermoplastic composites manufactured by compression molding, thermoforming, tape laying, or injection molding will play a major role due to their weldability, their suitability for automated production (robot), and their recyclability. To reach a further step of weight reduction, the use of carbon fiber reinforced polymer composites (CFRPC) is unavoidable. A full substitution of metal is unlikely and new developments will consist of a combination of metal and CFRPC. This paper shows new developments in joining hybrids of metal (steel DC01 and aluminum AlMg3) and CFRPC (organic sheets CF‐PA66 and CF‐PEEK). Induction heating is chosen as appropriate joining technology for the bonding of metal/CFRPC as it is characterized by a rapid heating. An explanation of the process, the equipment, the influence of surface treatments, the characterization of the bonding mechanisms, as well as a first step to automation are presented. Basic experiments on the influence of pretreatments and process parameters show great influence of corundum blasting, acidic pickling and temperature control on the shear tensile strength. Joints shear tensile strength of 14.5 MPa for AlMg3/CF‐PA66 and of 20 MPa for DC01/CF‐PEEK, respectively is measured. The documentation of the process parameters shows a high reproducibility and reliability of the developed equipment and demonstrator parts are successfully manufactured.